2003
DOI: 10.1097/01.brs.0000092461.11181.cd
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in the Decision to Perform a Selective Versus Nonselective Fusion of Lenke 1B and 1C (King-Moe II) Curves in Adolescent Idiopathic Scoliosis

Abstract: The characteristics of the compensatory "nonstructural" lumbar curve played a significant role in the surgical decision-making process and varied substantially among members of the study group. Side-bending correction of the lumbar curve to <25 degrees (defining these as Lenke 1, nonstructural lumbar curves) was not sufficientcriteria to perform a selective fusion in some of these cases. The substantial variation in the frequency of fusing the lumbar curve (6% to 33%) confirms that controversy remains about wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 22 publications
1
33
0
4
Order By: Relevance
“…This result is contradictory to the recommendations provided by the Lenke classification and thus the Lenke lumbar C modifier was termed a ''rule breaker''. Another study by Newton et al [29] showed that five AIS centers in the United States varied between 6 and 67% for selective thoracic fusions for Lenke 1C curves.…”
Section: Introductionmentioning
confidence: 99%
“…This result is contradictory to the recommendations provided by the Lenke classification and thus the Lenke lumbar C modifier was termed a ''rule breaker''. Another study by Newton et al [29] showed that five AIS centers in the United States varied between 6 and 67% for selective thoracic fusions for Lenke 1C curves.…”
Section: Introductionmentioning
confidence: 99%
“…3,20,38,43 With the evolution of spinal instrumentation and surgical techniques, STF has been shown to provide successful correction of the thoracic curve with spontaneous correction of the uninstrumented lumbar curve to allow for a well-balanced postoperative spinal column; 5,6,23,32,34,36,40,42 however, the risk for coronal decompensation remains a concern. 1,13,14,24,28,29,31,32,43 The decision to include the lumbar compensatory curve by performing a nonselective thoracic fusion (NSTF) may provide a "safer" option in the context of preventing revision surgery for coronal decompensation. 32 However, it must be weighed against the risk of an increased likelihood of back pain and degenerative changes with a more distal fusion into the mid-and lower lumbar spine.…”
mentioning
confidence: 99%
“…Improving thoracic kyphosis to maintain or improve lumbar lordosis has been recommended by previous authors [2,10,16,19]. Newton et al [17] reported that posterior segmental instrumentation for AIS significantly decreased thoracic kyphosis, which was also correlated to a loss of lumbar lordosis.…”
Section: Discussionmentioning
confidence: 97%
“…Such studies discuss stable and neutral vertebrae, coronal tilt of end vertebrae, selective thoracic fusion, and a variety of additional parameters that can be measured on straight and side bending radiographs [13][14][15][16]. There is a paucity of studies which analyze how to restore appropriate lumbar lordosis.…”
Section: Introductionmentioning
confidence: 99%